Beyond the Generalized Weakness: A Rare Case of Statin-Induced Immune-Mediated Necrotizing Myopathy - Leo Sakai DO; Hana Kazbour MD; James Huang MD (Journal of Investigative Medicine High Impact Case Reports)
Statin-induced immune-mediated necrotizing myopathy (IMNM) is a rare subtype of idiopathic inflammatory myopathy associated with statin exposure and characterized by positive anti-hydroxymethylglutaryl coenzyme A reductase antibodies. Here, we describe a case of a 66-year-old male who was admitted with the presumed diagnosis of rhabdomyolysis in the setting of chronic statin use but was later confirmed to have statin-induced IMNM after his symptoms were refractory to treatment. This case highlights the importance of having a high clinical suspicion for statin-induced IMNM when statin-associated muscle symptoms fail to resolve after the discontinuation of statins.